2016
DOI: 10.1093/schbul/sbv171
|View full text |Cite
|
Sign up to set email alerts
|

Tractography Analysis of 5 White Matter Bundles and Their Clinical and Cognitive Correlates in Early-Course Schizophrenia

Abstract: We observed white matter alterations in the right CB, ILF, and AF, possibly caused by myelin disruptions. The structural abnormalities interact with cognitive performance, and are linked to clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 81 publications
5
27
0
1
Order By: Relevance
“…Importantly, alterations of the ILF have also been associated with the presence of positive symptoms of psychosis in people with non-syndromic, early course (Ashtari et al, 2007, Seitz et al, 2016) and chronic schizophrenia (Phillips et al, 2009), as well as individuals with 22q11.2DS (Da Silva Alves et al, 2011). This is consistent with our finding of robust and tract - specific associations between alterations in FA (temporo-parietal component) and AD (temporo-occipital component) of the ILF and both positive and negative symptoms of psychosis in individuals with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, alterations of the ILF have also been associated with the presence of positive symptoms of psychosis in people with non-syndromic, early course (Ashtari et al, 2007, Seitz et al, 2016) and chronic schizophrenia (Phillips et al, 2009), as well as individuals with 22q11.2DS (Da Silva Alves et al, 2011). This is consistent with our finding of robust and tract - specific associations between alterations in FA (temporo-parietal component) and AD (temporo-occipital component) of the ILF and both positive and negative symptoms of psychosis in individuals with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…White matter abnormalities are diffuse in subjects with schizophrenia, with globally decreased levels of fractional anisotropy (FA) and increased radial diffusivity (RD) (Chavarria‐Siles et al, ; Reid et al, ), proxy measures for myelin integrity. Deficits are evident diffusely in frontomedial white matter tracts (Drakesmith et al, ), orbitofrontal cortex, posterior parietal cortex (Green et al, ), arcuate fasciculus, cingulum bundle, and inferior longitudinal fasciculus (Oestreich et al, ; Seitz et al, ). The apparently more global disruptions to white matter in schizophrenia compared to other neuropsychiatric disorders are consistent with the more severe and complex nature of dysfunction in schizophrenia.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Post‐mortem results show down‐regulated expression of white matter‐related genes and proteins as well as oligodendrocyte pathology (Beasley et al, ; Flynn et al, ; Hakak et al, ; Hercher, Chopra, & Beasley, ). Imaging studies also show decreased white matter volume as well as reductions in fractional anisotropy and diffusion tensor imaging, both imaging markers of white matter integrity (Agartz, Andersson, & Skare, ; Foong et al, ; Kubicki et al, ; McCarthy‐Jones et al, ; Samartzis, Dima, Fusar‐Poli, & Kyriakopoulos, ; Seitz et al, ; Whitford et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned white matter tracts connect regions of the brain that are abnormal in schizophrenia (Fornito et al, ; Friston, ). Specifically, imaging studies have demonstrated deficits in connectivity in schizophrenia patients in three white matter tracts of interest: the CC, the CB, and the arcuate fasciculus (AF; Agartz, Andersson, & Skare, ; Douaud et al, , ; Foong et al, ; Gasparotti et al, ; Kubicki et al, ; Kyriakopoulos, Bargiotas, Barker, & Frangou, ; McCarthy‐Jones et al, ; Price et al, ; Seitz et al, ; Whitford et al, ). Furthermore, deficits in the CC have been observed in first‐episode patients (Cheung et al, ; Dekker et al, ; Federspiel et al, ; Kyriakopoulos & Frangou, ; Perez‐Iglesias et al, ) and clinical high‐risk subjects (Hoptman et al, ).…”
Section: Introductionmentioning
confidence: 99%